Expression of Cathepsins B, D, and G in Extracranial Arterio-Venous Malformation - Hansen, Lauren; Brasch, Helen D.; Paterson, Erin; Patel, Josie; Bockett, Nicholas; Davis, Paul F.; Tan, Swee T. (Frontiers in Surgery, 2021)
Objectives: We have previously identified a population of cells that expressed stemness-associated markers in extracranial arterio-venous malformation (AVM) and demonstrated expression of cathepsins B, D and G on embryonic stem cell (ESC)-like populations in other vascular anomalies. This study investigated the expression of cathepsins B, D and G, and their localization in relation to this primitive population in extracranial AVM. Methods: Immunohistochemical staining was performed on AVM tissue samples from 13 patients to demonstrate expression of cathepsins B, D and G. Western blotting was performed on four AVM tissue samples and three AVM-derived primary cell lines to confirm protein expression of cathepsins B and D proteins. RT-qPCR was performed on three AVM-derived primary cell lines to demonstrate transcript expression of cathepsins B, D and G. Enzymatic activity assays were performed on three AVM-derived primary cell lines to investigate if cathepsins B and D were active. Localization of the cathepsins was investigated using immunofluorescence dual-staining of the cathepsins with the ESC markers OCT4 and SOX2, and mast cells marker chymase on two of the 13 AVM tissue samples. Results: Immunohistochemical staining demonstrated expression of cathepsins B, D and G in all 13 AVM tissue samples. Western blotting showed expression of cathepsins B and D proteins in all four AVM tissue samples and all three AVM-derived primary cell lines. RT-qPCR demonstrated transcripts of cathepsins B, D and G in all three AVM-derived primary cell lines. Enzymatic activity assays showed that cathepsins B and D were active. Immunofluorescence staining showed expression of cathepsins B and D on the OCT4+/SOX2+ endothelium and media of the lesional vessels and cells within the stroma in AVM nidus. Cathepsin G was expressed on the chymase+ phenotypic mast cells. Conclusions: This study demonstrated the novel finding of the expression of cathepsins B, D and G in AVM. Cathepsins B and D were expressed by the primitive population, and cathepsin G was localized to mast cells, within the AVM nidus.